IMPLEMENTASI PROGRAM TAHFIDZ AL-QUR’AN DI SDIT QURRATA A’YUN - Triary Abidareksa; Tri Ratna Dewi; Nor Kholidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the implementation of the Al-Qur'an Tahfidz program at SDIT Qurrta A'yun and to identify the supporting and inhibiting factors in its implementation. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects in this study consisted of the Principal, Al-Qur'an Tahfidz Teachers, Students, and Parents. The results of this study indicate that the Al-Qur'an Tahfidz program at SDIT Qurrata A'yun has been implemented since 2010 through the stages of planning, implementation, and evaluation. Planning includes setting a target of memorizing at least 2 juz, using modules, and involving parents. Implementation is carried out every Monday to Thursday with the Ilman Waa Ruhaan method and guided by competent Tahfidz Teachers. Evaluation of this program is assessed through three stages of evaluation, namely daily, semester, and annual. The evaluation results show that 65% of students achieve the memorization target. Supporting factors include the availability of bound books, teacher training, parental support, and an Islamic environment. Inhibiting factors include differences in student abilities, limited time, and unstable student enthusiasm.